P9 Train the trainers in situ simulation – technical best practice. (November 2018) - Gay, Christopher; Graby, Matthew; Websdale, Daniel; Blackmore, Andrew; Wright, David
Abstract : Introduction: In situ Simulations are viewed as higher impact than 'in-centre' simulation sessions, 1 but the nature of adapting 'in-centre' techniques to a broad range of environments with success can be difficult. HILS has developed an ' in situ ' focussed version of our Train the Trainers in Simulation course, which culminates in the delegates running their own in situ in Hull's Emergency Department (figure 1). For this, our technical team needed to consolidate our current training to be relevant for in situ simulation. This information is transferrable across many organisations, and is shared below. Method: Our method focused on 2 key technical elements of in situ simulation (audio visual and simulator) and their enhancement of learning, as well as tips for an efficient process of conducting the in situ simulation. We also encouraged delegates to get 'hands on' setting up the equipment. Summary of Key Information Points Delivered Audio Visual equipment brings 3 key enhancements - Control of scenario Distancing control can lead to a higher fidelity environment for delegate Observation of scenario Distancing observation can lead to a higher fidelity environment for the delegate, as well as allowing additional delegates to engage with the session from an adjacent location Video Debrief of scenario Enables audio visual reinforcement of key debriefing points Simulator use enables Risk Free Learning The ability to do harm to patients is greatly reduced or avoided completely Enhanced Feedback/Metrics Data such as compression rate and precise timings between decisions can enhance debriefing Higher Fidelity Tools Simulators can provide more realistic interactions than lower fidelity tools Process: Requesting Planning Pre–Event Setup Event Close down Results: Delegate feedback rated on a 7 point likert scale showed The 'technical considerations' session of the course was rated on average 6.3. The setting up session which featured delegates 'technical hands on' was rated on average 6.16. Pre and post course confidence in identifying technical considerations for an in situ was 2.6 and 5.5 respectively, showing an increase in technical confidence. Conclusion: In situ simulation can have many barriers to being successful, so any opportunity to minimise or avoid these barriers must be taken. Technology, when used properly, should enhance learning, rather than hinder it. We believe that HILS' way of engaging faculty will result in increased confidence in running in situ simulation, and better understanding of effective simulation processes. Reference: Fent G, Blythe J, Farooq O, et al . In situ simulation as a tool for patient safety: A systematic review identifying how it is used and its effectiveness. BMJ Simulation and Technology Enhanced Learning 2015;1:103–110.